Evolutionary Diversity Peaks at Mid-Elevations Along an Amazon-to-Andes Elevation Gradient - Griffiths, Andy R.; Silman, Miles R.; Farfan-Rios, William; Feeley, Kenneth J.; Cabrera, Karina García; Meir, Patrick; Salinas, Norma; Segovia, Ricardo A.; Dexter, Kyle G. (Frontiers in Ecology and Evolution, 2021)
Elevation gradients present enigmatic diversity patterns, with trends often dependent on the dimension of diversity considered. However, focus is often on patterns of taxonomic diversity and interactions between diversity gradients and evolutionary factors, such as lineage age, are poorly understood. We combine forest census data with a genus level phylogeny representing tree ferns, gymnosperms, angiosperms, and an evolutionary depth of 382 million years, to investigate taxonomic and evolutionary diversity patterns across a long tropical montane forest elevation gradient on the Amazonian flank of the Peruvian Andes. We find that evolutionary diversity peaks at mid-elevations and contrasts with taxonomic richness, which is invariant from low to mid-elevation, but then decreases with elevation. We suggest that this trend interacts with variation in the evolutionary ages of lineages across elevation, with contrasting distribution trends between younger and older lineages. For example, while 53% of young lineages (originated by 10 million years ago) occur only below ~1750 m asl, just 13% of old lineages (originated by 110 million years ago) are restricted to below ~1750 m asl. Overall our results support an Environmental Crossroads hypothesis, whereby a mid-gradient mingling of distinct floras creates an evolutionary diversity in mid-elevation Andean forests that rivals that of the Amazonian lowlands.